Information and computer technologies in distance teaching of foreign languages using social networks (for Tunisian audience) - Самі, Бен Ромдан (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2021)
The topic of the article concerns the application of information and computer technologies in teaching foreign languages, especially their adaptation to the conditions of distance learning. The author considers various approaches to the use of computer technologies in the current educational space and, in particular, the ways of working with some Internet tools in a Tunisian humanitarian higher education institution. The paper presents features of the Web 2.0 website as one of the possibilities to increase the volume of speech communication in a foreign language in distance learning as well as different types of Internet resources most popular among the students studying Russian in Tunisia. Hence, the author identifies and summarizes the specifics of introducing social networks as an additional platform for distance learning into the process of developing students' communicative competence. The objectives for describing the external factors that influence the improvement in methodological approaches to language teaching were the identification of the main ways for the engagement of the social networking services and integration of them into the structure of online lessons, i.e., selection of the country study material and development of methodological recommendations to bring it closer to the program topics, information exchange, and testing. There was applied the analytical method for researching the problems that students and teachers face in organizing the learning process based on digital assistance. It allowed classifying difficulties that hinder the successful integration of social media into learning. As a result, it was possible to identify the work rules for students and teachers, as well as the potential of Internet services which due to the development of databases and Internet infrastructure have facilitated the tasks for their users including teachers, as it is no longer necessary to acquire special knowledge and skills to create distant courses.